Anti-Corruption Prevention and Local Government Integrity Index in Balangan - Muhammad Helmi; Danang Biyatmoko; Muhammad Nur Iman Ridwan (Jurnal Ekonomi Pembangunan, 2026)
This study examines the effect of anti-corruption prevention programs on the local government integrity index and analyzes the role of public perceptions and experiences of integrity in Balangan Regency, Indonesia. A quantitative explanatory approach with a cross-sectional design was used. The anti-corruption prevention program was measured through the Monitoring Center for Prevention, while the integrity index was measured through the Integrity Assessment Survey. Public integrity perception and public integrity experience were positioned as moderating variables. Primary data were collected through questionnaires from 300 public service users, and secondary data were obtained from official MCP and SPI scores. Data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The results show that anti-corruption prevention programs have a positive and significant effect on the integrity index. Public integrity perception also has a positive direct effect, while public integrity experience has no significant effect. However, neither perception nor experience moderates the relationship. These findings imply that anti-corruption prevention should move beyond administrative compliance toward public-oriented accountability.